Effect of Spraying the Vigna Radiata L.Plant, with Salicylic Acid and Boron on Yield and Protein Percentage - Al-Bayaty, Ayyub J.; Hatem, Noas Ahmed (Academia Open, 2025)
This study was conducted for the period from 1 Nomber 1to 15 April for the 2023 season to determine the effect of Salicylic acid and Boron on Vigna radiata plant yield and protein percentage. Concentrations of (0, 50,75 and 100,).and boron with (0, 25 and 50) mg L-1distile water were used sprayed on plants grown in plastic pots using the CRD design. The results showed: The treatment spraying with salicylic acid by 100 and boron by 50mg L-1 concentration mg.L-1 distilled water gaved The highest values for yield triats (number of pods.plant-1, number of seeds.pod-1, weight of 100 seeds.g, seed yield Plant -1 gm , harvest index and protein percentage) reached (9.0, 7.44, 10.99, 29.40 , 62.99 and), while the lowest values were in the Control treatment (without spraying with salysic acid boron) and were (3.99, 4.99, 10.0, 23.99 , 51and 32) respectively. Highlights: Study salicylic acid and boron effects on Vigna radiata yield. 100mg salicylic acid + 50mg boron maximized yield traits. Treatment improved pods, seeds, protein, and harvest index significantly. Keywords:Vigna radiate; salysilic acid; boron